The Correlation Between Fasting Blood Glucose Levels and Creatinine Levels in Diabetes Mellitus Patients - Sarjono, Mieke Antari; Anak Agung Ayu Eka Cahyani; Putu Ayu Parwati (CV. CENDIKIA JENIUS INDONESIA, 2025)
Diabetes mellitus is a chronic condition caused by high blood glucose levels due to the pancreas's inability to produce sufficient insulin. Elevated blood glucose levels cause the kidneys to work harder in the blood filtration process. Creatinine testing is one of the indicators used to detect kidney damage. This study aims to determine the correlation between fasting blood glucose levels and creatinine levels in patients with diabetes mellitus at Bhayangkara Hospital Denpasar. This study is an analytical observational research employing a questionnaire method and direct examination, conducted in March and April 2025. A total of 48 samples were included using the total sampling technique. Data were analyzed using the Spearman Rank correlation test. The results showed that 40 subjects (83.3%) had high fasting blood glucose levels and 8 subjects (16.7%) had normal levels. Meanwhile, 39 subjects (81.2%) had high creatinine levels and 9 subjects (18.8%) had normal levels. The results of this study indicate a significant relationship between fasting blood glucose levels and creatinine levels in patients with diabetes mellitus at Bhayangkara Hospital Denpasar, with a p-value of 0,000 and a correlation coefficient of 0,501, indicating a positive relationship.It is concluded that hyperglycemia plays a role in the decline of kidney function. Patients are advised to maintain a healthy lifestyle, healthcare providers to enhance education, and future research to consider complication factors and therapy.